Kitab al-Tafsir wal Mufassirun dan Pengaruhnya dalam Kajian Tafsir - Ahmad Nabil Amir (Jurnal Iman dan Spiritualitas, 2021)
Kitab Al-Tafsir wa’l-Mufassirun by Dr. Muhammad Husayn al-Dhahabi is an important work in tafsir which offers substantive analysis on the foundational history and tradition of tafsir. It analyzed certain major patterns of tafsir and comprehensively surveyed early development of its science, method, and character of classical and contemporary work in defining and analyzing the Quranic text. The work also highlights the classical impact of tafsir in the development of some unprecedented work in the tradition of tafsir. The major contribution of this work is to highlight certain un-reknown and un-discovery work of tafsir which was developed in the declining era of Islam. The principal idea is to compare various style and method of tafsir including the method of ijtima‘i, sufi, haraki, shi‘i, ra’yi, athari, ‘ilmi, mazhabi, adabi and ijtihadi. This paper will discuss the contribution of Dr. Muhammad Husayn al-Dhahabi in producing his monumental work, Al-Tafsir wa’l-Mufassirun and its ramification and reverberating impact in contemporary discourse of tafsir.